Řízení rizik ve společnosti AT CAR, s.r.o. - Kumstát, Petr (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2017)
Diplomová práce se zabývá řízením rizik ve společnosti AT CAR, s.r.o., se zaměřením na brněnskou pobočku. Pro řízení rizik je důležitá identifikace, analýza a snižování rizik. Tento proces je popsán v teoretické části, včetně pojmů souvisejících s danou tématikou. V analytické části jsou identifikována rizika, zejména pomocí SLEPTE analýzy, Porterovy analýzy a 7S modelu. Nalezená rizika jsou hodnocena skórovací metodou. Poslední část je věnována návrhům opatření pro snížení rizik.

Risk management in company AT CAR, s.r.o. with focus on its branch Brno is the main topic of this thesis. As for the risk management itself, the most important tasks are identification, analysis and reducing the possible risks. These processes are described and discussed in the theoretical part of the thesis, while it also introduces all important terms related to this topic. In the analytical part, the risks are identified using appropriate methods such as SLEPTE analysis, Porter’s Five Forces and 7S model. The risks identified are thereafter evaluated using the scoring method. In the last part, recommendations and measures for reducing the risk are presented.
Risk Management in the company AT CAR, s.r.o.
Keywords: Rizika; řízení rizik; identifikace rizik; analýza rizik; snižování rizik.; Risks; risk management; risk identification; risk analysis; risk reduction.